THE APPLICATION OF EXPERIMENT LEARNING ON THE LEARNING MATERIAL AUTOMOTIVE ELECTRICAL ON GRADE X SMK NEGERI 1 PALANGKA RAYA ACADEMIC YEAR 2014/2015 - Falentino Piscesco; Wiyogo (Jurusan Pendidikan Teknologi Dan Kejuruan, 2015)
ABSTRACT Experimental method is a way of presenting the lesson material where students conduct experiments with his own experience to address a question or hypothesis being studied. The study involving 38 students of class X TKR SMK-1 Palangka Raya that were chosen as respondents. The instrument used is the result of Cognitive learning Tests, Teacher and Student Activities Observation Sheet, Student Response Questionnaire and Observation Sheet of Psychomotor Performance, and analyzed using descriptive techniques. Data on student response obtained after the material has been taught by experimental method. Data on student activities and psychomotor performance were obtained from student’s practice performance in the workshop. The analysis of the results showed the completeness on cognitive learning on 35 students that has completed (92%) and 3 students has not complete (8%) of the 38 students who took the tests. Classically, the learning is said completed since there are 92% o fall students completed their study. Student’s response of the experimental method on psycho motoric performance, of the 38 students there are 34 students who has completed and 4 students who has not completed and the average score obtained is 3.0 which is good since it has passed the minimum KKM of 2,67.